2022
DOI: 10.1371/journal.pntd.0010680
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug effects among students following mass de-worming exercise involving administration of Praziquantel and Albendazole in KEEA Municipality, Ghana

Abstract: Background To manage the deleterious effects of parasitic infections such as lymphatic filariasis (LF) and schistosomiasis among school children, most countries including Ghana make use of mass drug administration (MDA). Although MDA has proven effective in reducing worm burden, unfortunately adverse drug effects (ADEs) post-MDA are derailing the gains and also remain poorly monitored. The study assessed incidence and factors associated with ADEs among students following a school-based mass de-worming exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, as observed in this study, fear of side effects of the drugs used in MDA has been reported to cause hesitation in people to take the medications. 27 , 28 A study in Tanzania reported that participants claimed that MDA medications are given for free, so they have hidden agendas, such as killing generation by affecting fertility. 13 To increase the participation of the community, issues related to trust, adoption of local conditions, minimizing adverse effects of the drugs, promotion of the broad benefit of MDA and addressing challenges of systematic compliance, should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as observed in this study, fear of side effects of the drugs used in MDA has been reported to cause hesitation in people to take the medications. 27 , 28 A study in Tanzania reported that participants claimed that MDA medications are given for free, so they have hidden agendas, such as killing generation by affecting fertility. 13 To increase the participation of the community, issues related to trust, adoption of local conditions, minimizing adverse effects of the drugs, promotion of the broad benefit of MDA and addressing challenges of systematic compliance, should be addressed.…”
Section: Discussionmentioning
confidence: 99%